Strength Analysis of Crusher Construction in Nyamplung Seed Peeling Machine Using the Finite Element Method - Nandang Imam Santosa; Asep Dharmanto; Asep Saepudin; Wilarso (JOURNAL OF MECHANICAL ENGINEERING MANUFACTURES MATERIALS AND ENERGY, 2024)
The nyamplung seed peeling machine uses a single roll crusher as its operating principle to automatically separate the nyamplung fruit's shell. One of the crucial parts of this apparatus that breaks down the nyamplung fruit shells is the crusher. The issue arises from the fact that the strength of the material utilized to construct the crusher is still unknown. This raises questions regarding how well the Nyamplung bean peeling machine crusher will function if it is used constantly. The purpose of this study is to identify the kind of material that works well for a nyamplung seed peeling machine crusher. An analysis will be conducted to ascertain the strength of the Nyamplung seed peeling machine crusher to follow up on this issue. The finite element method was used to conduct the testing. ASTM A36 and AISI 304 are the two materials that are compared in this analysis. In addition, it can be used to compare two different types of materials in terms of their strength, cost, and degree of safety. Following analysis for manual shaft calculations utilizing AISI 304 and ASTM A36 materials. With a yield strength of 250 N/mm², a safety factor of 9, a displacement of 0.022 mm, and von Mises stress readings of 29.044 N/mm² were achieved from the crusher simulation utilizing ASTM A36 material. Von Mises stress for the AISI 304 material was 28.471 N/mm², displacement was 0.023 mm, safety factor was 7, and yield strength was 206.804 N/mm².